Hubungan Bullying Dengan Kesehatan Mental Dan Perilaku Sosial Pada Santriwati Di Pondok Pesantren Manbail Futuh Jenu Tuban - Shobiati Maruroh; Lukman Hakim; Miftahul Munir; Tiara Putri Ryandini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Bullying frequently occurs among adolescents, particularly in boarding school environments such as Islamic boarding schools, and may negatively affect mental health and social behavior. This study aimed to analyze the relationship between bullying, mental health, and social behavior among female students at Manbail Futuh Islamic Boarding School, Jenu, Tuban. This study used a correlational analytic design with a cross-sectional approach. The population consisted of all female students, with 106 respondents selected using total sampling. Data were collected using structured questionnaires measuring bullying, mental health, and social behavior, and were analyzed using Spearman’s rho correlation test with a significance level of α = 0.05. The results showed a significant relationship between bullying and mental health (p = 0.000; r = 0.593) and between bullying and social behavior (p = 0.000; r = 0.613). In conclusion, bullying was significantly associated with mental health and social behavior among female students. Prevention and appropriate intervention are needed to promote positive mental health and social behavior.